IBM FlashSystem 9500 product guide - Larsen, Carsten; Lottering, Corne; Terwisga, Douwe van; Lonzer, Hartmut; Herd, Jon; Williams, Kendall; Trojok, Konrad; Mookerjee, Shu; Gucer, Vasfi (IBM redbooks., 2023)
This IBM® Redpaper® Product Guide describes the IBM Storage FlashSystem® 9500 solution, which is a next-generation IBM Storage FlashSystem control enclosure. It combines the performance of flash and a Non-Volatile Memory Express (NVMe)-optimized architecture with the reliability and innovation of IBM FlashCore® technology and the rich feature set and high availability (HA) of IBM Storage Virtualize. Often, applications exist that are foundational to the operations and success of an enterprise. These applications might function as prime revenue generators, guide or control important tasks, or provide crucial business intelligence, among many other jobs. Whatever their purpose, they are mission critical to the organization. They demand the highest levels of performance, functionality, security, and availability. They also must be protected against the newer threat of cyberattacks. To support such mission-critical applications, enterprises of all types and sizes turn to the IBM Storage FlashSystem 9500.